GROWTH RESPONSE AND NITROGEN USE EFFICIENCY OF PALM OIL VARIETY ON N FERTILIZING IN PRE NURSERY - wilda lumban tobing; Chairani Hanum; Edy Sigit Sutarta (Agric, 2018)
Oil palm plantation expansion in Indonesia continue to increase year by year. Several varieties of oil palm have been produced but not much information about the growth characteristics. Urea as nitrogen fertilizer has become a staple for the cultivation cycle of oil palm. The determination of nitrogen use efficiency (NUE) on palm oil varieties can be used to find out N requirement of each plant according to their needs. This research was aimed to analyze the growth response and NUE of palm oil varieties to fertilizer N at pre nursery. It was conducted in nursery area at Yos Sudarso Binjai Street and Pusat Penelitian Kelapa Sawit, Medan from November 2016 until March 2017 using Completely Randomized Block Design followed by Scott Knott test at α = 5%. There were 35 treatment combinations that used seven varieties of Dura x Pisifera Medan Palm Oil Research Center (AVROS, Simalungun, PPKS 540, Yangambi, PPKS 718, PPKS 239, and Langkat) with N consisting of 5 levels (0 ; 0,5 g ; 1 g; 1.5 g and 2 g). The results showed that the application of N fertilizer influence significant effect on the growth of stem circumference and the number of leaves. The highest of nitrogen use efficiency is found in Simalungun varieties with N application of 1,5 g/plant.